Mineral rich algae with pine bark improved pain, physical function and analgesic use in mild-knee joint osteoarthritis, compared to Glucosamine: a randomized controlled pilot trial - Shane Heffernan (Complementary Therapies in Medicine, 2020)
IntroductionOsteoarthritis (OA) is characterised by synovial joint pain, functional disability and affects ∼13% of people worldwide, of which ∼16-27% report Knee-OA (KOA). Glucosamine (Glu) is the most widely used nutraceutical treatment for OA despite a lack of scientific consensus, therefore alternative nutraceutical treatments are required. The aim of this study was to investigate the effect of Lithothamnion species, seawater-derived magnesium and pine bark (Aq+) on pain, symptoms and improve physical function in symptomatic (sKOA), compared to Glu.Methods358 participants were screened. In a double-blinded crossover pilot-trial, sKOA participant (n = 30) were randomly assigned to either the Glu group (2000 mg day-1) or Aq+ (3056 mg day-1) for 12 weeks (clinicaltrials.gov:NCT03106584). The Knee Injury and Osteoarthritis Outcome Score was used to assess subjective pain and symptoms. Timed-up-and-Go (TuG) and Six minute walking distance were used to assess functional change and analgesic use was recorded.ResultsAq+ improved pain, with a large effect (P < 0.01, d’ = 0.73, 95%CI 0.201-1.265) and no change for Glu (d’ = 0.38, P = 0.06). Only Aq+ improved pain (P < 0.05) for males (d’ = 0.91, 95%CI 0.162-1.667) and females (d’ = 0.55, 95%CI 0.210-1.299). In females, Aq+ improved TuG by -7.02% (d’ = 0.92, 95%CI 1.699-0.141) while Glu worsened performance by 4.18% (P = 0.04). Aq+ reduced analgesia by 71.6%, compared to Glu (P = 0.02; d’ = 0.82, 95%CI 1.524-0.123). Aq+ was superior to Glu at improving pain, KOOS subscales, physical function and analgesia use in mild-sKOA. Given these data, Aq+ should be considered as a supplementary treatment for early-stage-KOA and may have the potential to reduce use of pain medication, although larger replication studies are required.